Bis(acetone 4-phenylthiosemicarbazonato-κ(2) N (1),S)zinc(II) - Tan, Kong Wai (International Union of Crystallography, 2009)
The Zn(II) atom in the title compound, [Zn(C(10)H(12)N(3)S)(2)], is N,S-chelated by the deprotonated Schiff base in a tetrahedral environment. The metal atom lies on a twofold rotation axis that relates one anion to the other. The amino H atom forms an intermolecular N—H⋯π interaction to an aromatic ring.